Ergonomic Exercise Effects on Cholesterol in Elderly in LKS (Social Welfare Agency) Love House Jambon - Yalestyarini, Eva Agustina; Hana, Nurjannah; Ririn Nasriati; Muftiana, Elmie (Journal of Global Research in Public Health, 2024)
Elderly (elderly) is a part of the process of human development. As we get older, physiological functions decrease which causes various health problems. One of the health problems in old age is an increase in blood cholesterol levels. Total cholesterol in the blood increases with the aging process. One way to reduce cholesterol levels is to do ergonomic exercises to restore or correct the position and flexibility of the nervous system and blood flow. The purpose of this study was to analyze the effect of ergonomic exercises on cholesterol levels in the elderly at LKS Rumah Kasih Jambon. The research design is a quantitative quasy experiment with a one group pretest posttest design approach. The sample in this study were 15 respondents who were given routine ergonomics exercise 4 times a week for 2 weeks. Sampling in this study was carried out in a non-probability way using a purposive sampling technique. The results of the Paired Sample t-test statistic showed that there was an effect of ergonomic exercise on cholesterol levels in the elderly at the Jambon Love Care Center with p value = 0.000 (p <0.05). The results showed that the average blood cholesterol levels before and after the ergonomic exercises were 240.73 mg/dl and 230.40 mg/dl. The difference in cholesterol levels before and after ergonomics exercise was 10.33 mg/dl.